The Comparative Effects of Anakinra and Tocilizumab on Inflammation and Cerebral Vasospasm in an Experimental Subarachnoid Hemorrhage Model - Güven Kılıç; Berk Enes Engin; Amir Halabi; Cengiz Tuncer; Mehmet Ali Sungur; Merve Alpay; Adem Kurtuluş; Hakan Soylu; Ali Gök (Medicina)
Objective: Subarachnoid hemorrhage (SAH) is a life-threatening cerebrovascular condition that triggers a robust inflammatory response and cerebral vasospasm. This study aimed to evaluate the effects of anakinra, an interleukin-1 receptor antagonist, and tocilizumab, an interleukin-6 receptor antagonist, on inflammation and vasospasm in an experimental rat SAH model. Methods: Forty male Sprague Dawley rats (200–250 g) were randomly assigned to five groups: control, SAH, SAH + anakinra (ANA), SAH + tocilizumab (TCZ), and SAH + anakinra + tocilizumab (ANA+TCZ). SAH was induced by injecting non-heparinized arterial blood into the cisterna magna. Treatment groups received anakinra (50 mg/kg twice daily), tocilizumab (8 mg/kg once daily), or their combination for three days. Blood and cerebrospinal fluid (CSF) samples were analyzed for inflammatory markers (IL-1, IL-6, TNF-α, CRP), and histopathological evaluations were conducted to assess vasospasm and apoptosis. Results: SAH significantly increased pro-inflammatory cytokines (IL-1, IL-6, TNF-α, CRP) and fibrinogen levels in serum and CSF while reducing the basilar artery lumen diameter (p < 0.001). Anakinra and tocilizumab treatments significantly reduced inflammatory markers and vasospasm severity compared to the SAH group (p < 0.05). Combination therapy was more effective in reducing inflammation and vasospasm than either treatment alone (p < 0.05). Anakinra showed a stronger effect on IL-1 reduction, while tocilizumab was more effective in lowering IL-6 levels. The ANA+TCZ group exhibited a significant decrease in caspase activity, indicating reduced apoptosis (p < 0.05). Conclusions: Anakinra and tocilizumab effectively mitigated inflammation and vasospasm in an experimental SAH model, with combination therapy showing superior efficacy. These findings suggest that targeting both IL-1 and IL-6 pathways may be a promising therapeutic strategy for managing SAH complications. Further studies are warranted to evaluate long-term outcomes and clinical implications.